Analysis expectation of investment projects in the conditions of maintenance of investment security companies: probabilistic approach - G.V. Berlyak (Vìsnik Žitomirsʹkogo Deržavnogo Tehnologìčnogo Unìversitetu: Ekonomìčnì Nauki, 2015)
Uncertainty in making investment and financial decisions arises both because there are many alternatives that can select an investor, and through him the uncontrollable state of the environment at the time of implementation of the decision. One of the stages of the economic analysis is the study now necessary volume of investment resources, possibly based on the analysis of performance indicators of investment security.